PENYULUHAN ADMINISTRASI PERPUSTAKAAN MI DARUL HUDA CODO KECAMATAN WAJAK KABUPATEN MALANG - Annisa Arifatur Rohmah; Fitria Kusuma Dewi (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2022)
The library is one of the government agencies that support the level of education and as an information institution that is used as a place to explore one's potential through reading and recreational facilities. Libraries will optimize services in four areas, namely learning activity facilities, information facilities, research facilities, and recreational facilities. To maximize library services to users, this library administration extension activity was selected as a program to develop and operate libraries in schools. The objectives of counseling are to optimize library operations, increase library utilization in MI, increase students' motivation and interest in reading, and improve library management. The activities have been carried out and have achieved 100% of the expected results. Counseling was given to librarians and also students. Counseling for students about rules, how to borrow, how to return and also an explanation of borrowing cards. While counseling to administrators is about all library administration, starting from when books are entered, book coding, book classification, borrowing and returning books.